Impact of selected factors on employees' satisfaction and organisational performance - Dupe Adesubomi Abolade (Trends Economics and Management, 2020)
Purpose of the article: The general objective of this study was to examine the impact of working tools, training, organisation's physical environment, organisational communication and organisational structure on employees' job satisfaction and organisational performance. Methodology: The study adopted random sampling technique in selecting the participants. Self-structured questionnaires were used to elicit information from a sample size of one hundred and thirty-two respondents. One hundred and twenty-five instruments were properly completed and fit for analysis. Scientific aim: This study investigated the impact of some selected factors (working tools, training, organisation's physical environment, organisational communication, and organisational structure) in determining job satisfaction of employees and organisational performance. Findings: The study found out that working tools, training, work environment, organisational communication and organisational structure significantly affected employees' satisfaction and organisational performance. Conclusions: It was recommended that management and other decision makers in organisations should pay good attention to effective communication, conducive work environment, and appropriate organisational structure, provide appropriate tools for the employees, and give right training to the employees; these would enhance employees' satisfaction and also improve the performance of the organisation.
Keywords: L16; L19; L25; L68; M53; 650; work environment; organisational structure; employee satisfaction; organisation's performance